Existence of entropy solution for a nonlinear parabolic problem in weighted Sobolev space via optimization method - Hmidouch, Lhoucine; Jamea, Ahmed; Laghdir, Mohamed (Mathematical Modelling and Analysis, 2023)
This paper investigates the existence result of entropy solution for some nonlinear degenerate parabolic problem in weighted Sobolov space with Dirichlet type boundary conditions and L1 data.